THE ROLE OF DIGITAL TECHNOLOGIES IN THE DEVELOPMENT OF MARKETING DEPARTMENT ACTIVITIES IN HIGHER EDUCATION INSTITUTIONS - Makhmudov Rashid Alisherovich (Uzbekistan Open Conference, 2026)
The article examines the impact of digital technologies on the development of marketing departments in higher education institutions. The study analyzes modern digital tools for promoting educational services, the application of analytical systems and the transformation of communication processes in the context of the digital economy. Key directions for improving the effectiveness of university marketing activities based on a data-driven approach are identified. The problems and prospects of digital transformation of marketing in higher education are determined.
Keywords: digital technologies; university marketing; digital transformation; educational services; internet marketing; data analytics; university brand